Identification of Victims Response to Bullying Cases: A Study of Javanese Students - Chr Argo Widiharto; Dewi Retno Suminar; Wiwin Hendriani (Journal of Educational, Health and Community Psychology, 2020)
Bullying is an incident that frequently involves a perpetrator, bystander, and victim. However, victims’ responses to stop bullying, does not always achieve the expected outcome. This is partly because the responses vary significantly, and victims does not explicitly show their intention. The purpose of this research is to identify the types of bullying victims’ responses and identify which among them should be implemented. The sample are Javanese 4th to 6th-grade elementary school students who have witnessed bullying. The total sample of 290 students were taken from the elementary schools in Semarang, Yogya, Wonosobo, Pemalang, and Tegal. The dominant victim response is helplessness and there is no difference between cities and classes.Keywords: identification of responses, victims of bullying, victim responses, Javanese student